A rare prostatic tumour masquerading clinically as benign prostatic hyperplasia - Kundargi, Vinay S.; Patil, Siddanagouda B.; Patil, Santosh R.; Shukla, Vikas (International Journal of Research in Medical Sciences, 2024)
Prostatic tumours are usually benign. Malignant tumours are usually adenocarcinoma. Rare benign prostate tumours include inflammatory myofibroblastic tumours, which can be found in various body parts and are frequently identified in the lung or abdominal cavity of children and young adults. Inflammatory myofibroblastic tumours of the urinary tract present more often in kidneys. Prostatic inflammatory myofibroblastic tumours are sporadic and rare. Presenting 44 years old male with complaints of gross hematuria for 15 days with recurrent urine retention. Per rectal examination revealed, grade II prostate enlargement was firm in consistency. PSA was mildly raised (4.4 ng/ml). Ultrasound abdomen showed enlarged prostate (volume -40 cc) with irregular margins and heterogeneous echo texture showing increased flow on colour Doppler. Transrectal ultrasound (TRUS) showed a well-defined irregular heterogeneously echoic mass in the transitional zone, but TRUS biopsy showed no malignancy. After TURP, prostate chip examination showed inflammatory myofibroblastic pseudotumour of the prostate. Diﬀerentiation of inflammatory myofibroblastic prostate tumours from malignant tumours through imaging and laboratory tests is diﬃcult. A case of prostatic inflammatory myofibroblastic tumour observed after transurethral resection of the prostate to treat prostate hyperplasia in a 44-year-old man is presented in this report.